2017
DOI: 10.1002/2017gb005681
|View full text |Cite
|
Sign up to set email alerts
|

Basin scale variability of active diazotrophs and nitrogen fixation in the North Pacific, from the tropics to the subarctic Bering Sea

Abstract: Nitrogen‐fixing microorganisms (diazotrophs) provide biologically available nitrogen to plankton communities and thereby greatly influence the productivity in many marine regions. Various cyanobacterial groups have traditionally been considered the major oceanic diazotrophs, but later noncyanobacterial and presumably heterotrophic diazotrophs were also found to be widespread and potentially important in nitrogen fixation. However, the distribution and activity of different diazotroph groups is still poorly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
123
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 57 publications
12
123
4
Order By: Relevance
“…While Chavez et al (1995) focused solely on Chlorophyll a containing cells (prochlorophytes with 0.54-0.67 µm equivalent spherical diameter) and primary production measurements, Nayar and Chou (2003) used scanning electron microscopy and showed that the borosilicate glass microfibers get compacted during combustion, which effectively downsizes the nominal pore size. The only obvious explanation for the discrepancy to our results is that Nayar and Chou (2003) combusted their filters at 600 • C for 1 h, while most studies carrying out BNF measurements (including our present one) combusted filters at 450 • C for 2-12 h (e.g., Montoya et al, 1996;Capone et al, 2005;White et al, 2007;Farnelid et al, 2013;Shiozaki et al, 2017). While the lower temperature of 450 • C is enough to eliminate carbon or nitrogen contamination from filters, it apparently compacts the filter fiber structure less than at 600 • C. Manufacturers advise maximum temperatures of 500 • C for borosilicate membranes, and Nayar and Chou (2003) observed melting of the filters when exposing them to >600 • C or to longer durations of combustion.…”
Section: Different Retention Characteristics Of Gf/f and Advantec Filcontrasting
confidence: 82%
“…While Chavez et al (1995) focused solely on Chlorophyll a containing cells (prochlorophytes with 0.54-0.67 µm equivalent spherical diameter) and primary production measurements, Nayar and Chou (2003) used scanning electron microscopy and showed that the borosilicate glass microfibers get compacted during combustion, which effectively downsizes the nominal pore size. The only obvious explanation for the discrepancy to our results is that Nayar and Chou (2003) combusted their filters at 600 • C for 1 h, while most studies carrying out BNF measurements (including our present one) combusted filters at 450 • C for 2-12 h (e.g., Montoya et al, 1996;Capone et al, 2005;White et al, 2007;Farnelid et al, 2013;Shiozaki et al, 2017). While the lower temperature of 450 • C is enough to eliminate carbon or nitrogen contamination from filters, it apparently compacts the filter fiber structure less than at 600 • C. Manufacturers advise maximum temperatures of 500 • C for borosilicate membranes, and Nayar and Chou (2003) observed melting of the filters when exposing them to >600 • C or to longer durations of combustion.…”
Section: Different Retention Characteristics Of Gf/f and Advantec Filcontrasting
confidence: 82%
“…These authors do note that observations of Trichodesmium were relatively rare events and when observed they were clumped and unevenly distributed on the filters. Additionally, Venrick (1974) recorded up to 2,000 heterocysts L −1 in early transects of the NPSG, and gene-based abundance herein and elsewhere have also reported nifH phylotypes belonging to heterocystous symbionts on the order of ∼1000's L −1 (Church et al, 2009;Shiozaki et al, 2017). Keeping in mind the large differences in methodology between prior studies and our own, heterogeneity and aperiodicity appear to be the norm for these large diazotrophs.…”
Section: Month-yearsupporting
confidence: 67%
“…Alternately, if the export ratio is more consistent with measured ratios (e = 0.02-0.15), then either large diazotroph production would need to be an order of magnitude greater than what we have estimated or other N 2 -fixing organisms are directly or indirectly contributing to the summer export pulse. While not observed in our study period, there is precedent in the literature for an order of magnitude increase in the concentration of large diazotrophs as discussed earlier (Venrick, 1974;Church et al, 2009;Pasulka et al, 2013;Shiozaki et al, 2017) and presumably their contribution to production and export. And so, while DDA cell abundances were relatively low over our study period and the disparity between cell-and gene-based abundance needs to be reconciled, there are historical records of abundances that are more consistent with summer DDA-driven export than ours.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…ARA = acetylene reduction assay.LocationSurface N 2 fixation rate (nmol N L −1 d −1 )MethodDominant Diazotroph (s)ReferencenSCS and ECS Kuroshio1.14–10.40ARAUnicellular diazotrophsThis studynSCS coastal upwelling0.1–5.6 15 N 2 gas bubbleUnknow 28 SCS (Mekong River plume)0.59–22.77 15 N 2 gas bubble Trichodesmium spp. and DDAs 63 Western North Pacific≈0.3–22ARAUnicellular diazotrophs 64 North Pacific0.360–3.05 15 N 2 gas bubbleHeterotrophic bacteria 65 Northeast Atlantic<0.4ARAUnicellular diazotrophs 66 Eastern North Atlantic0–151.2 15 N 2 gas bubble Trichodesmium and UCYN-A 67 Arabian Sea0.8–225 15 N 2 gas dissolution Trichodesmium bloom 68 Indian Ocean0.18–1.27 15 N 2 gas bubbleHeterotrophic bacteria 69 …”
Section: Discussionmentioning
confidence: 99%